1991
DOI: 10.1007/bf02190705
|View full text |Cite
|
Sign up to set email alerts
|

Angioarchitectonics of the venous vessels and morphological changes in coronary heart disease

Abstract: For an understanding of the effects of myocardial protection via the coronary sinus and other cardiac veins, study of the angioarchitectonic of these veins in ischemic hearts is of special interest. Venous vessels were filled with radiological contrast material (hearts of decreased patients who died from coronary disease and also normal hearts) and were then studied using the microhistoangiographic technique. It was noted that necrotic zones of the histologic preparations were similar to the corresponding micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…It has been shown that the thebesian vessels have an increased diameter with chronic myocardial infarction. In patients with congestive heart failure, congestion is mainly in large veins, not the thebesian vessels (13). Sinusoids are large capillaries with varying morphology.…”
Section: Lesser Cvs (Thebesian Vessels)mentioning
confidence: 99%
“…It has been shown that the thebesian vessels have an increased diameter with chronic myocardial infarction. In patients with congestive heart failure, congestion is mainly in large veins, not the thebesian vessels (13). Sinusoids are large capillaries with varying morphology.…”
Section: Lesser Cvs (Thebesian Vessels)mentioning
confidence: 99%
“…A veia cardíaca média acompanha paralelamente o RIvS, e contribui no retorno vascular do órgão. Veias menores, denominadas de tebesianas, se abrem em forames venosos mínimos, diretamente nas quatro câmaras do coração, principalmente na parede dos átrios e em menor quantidade, na parede dos ventrículos (RATAJCZYK-PAKALSKA, 1990;DYCE, 2019;LARSSON, 2020;KÖNIG, 2021)…”
unclassified